Pengaruh Profitabilitas, Struktur Modal Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan - Pramesti, Farida Arrum; Rizki, Tabah (JCA (Jurnal Cendekia Akuntansi), 2024)
The aim of this research is to analyze the influence of variables that influence company value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The variables used are profitability, capital structure, and managerial ownership. This research uses a purposive sampling method in selecting the research sample. Hypothesis testing was carried out using multiple linear regression analysis which was processed using statistical testing tools in the form of IBM SPSS Version 29. The results of testing on three variables can be concluded that profitability and managerial ownership have an effect on company value, while capital structure has no effect on the company.